Gene therapy: basics and therapeutic applications - Khurana, Amit (Henry Stewart Talks, 2023)
Introduction to gene therapy, Basic concepts of gene therapy, Methods of gene transfer, Ex vivo and in vivo gene transfer, Therapeutic applications of gene therapy